Antiplatelet therapy only, without anticoagulation, for percutaneous coronary intervention: A translational application of platelet slip. Issue 6 (2021) - Denardo, Scott J.; Parish, Alice; Green, Cynthia L.; Oxendine-Phillips, Latasha; Tcheng, James E.
No abstract available